2016
DOI: 10.1515/msp-2016-0044
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of X-ray structure, dielectric properties and AC conductivity of (4E)-2-amino-3-cyanobenzo[b]oxocin-6-one

Abstract: The crystal structure of (4E)-2-amino-3-cyanobenzo [b]oxocin-6-one, denoted as 4(E)-ACBO, was analyzed using X-ray diffraction technique. The dielectric and AC electrical conductivity measurements of the bulk 4(E)-ACBO in the form of pellet were studied in the range of frequency 42 Hz to 5 MHz and the temperature range of 303 K to 373 K. The temperature and frequency dependence of dielectric constant (ε 1 ), dielectric loss (ε 2 ) and AC electrical conductivity (σ AC ) were investigated. The relaxation time (τ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Inset of Fig. 8c shows the temperature variation of τ and it is found to follow the Arrhenius behavior given as: [48][49][50]…”
Section: Impedance Spectroscopymentioning
confidence: 86%
“…Inset of Fig. 8c shows the temperature variation of τ and it is found to follow the Arrhenius behavior given as: [48][49][50]…”
Section: Impedance Spectroscopymentioning
confidence: 86%
“…Fig. 11 shows the temperature variation of τ, it is observed that the relaxation time follows Arrhenius behavior given as: [42,43,44]…”
Section: Impedance Spectroscopymentioning
confidence: 99%
“…13. The relaxation time is distributed and suggests that the relaxation mechanism is thermally activated in nature and follows Arrhenius behavior given by: [42,43,44]…”
Section: Electrical Modulusmentioning
confidence: 99%